Ex-Vivo Trans-Corneal and Trans-Scleral Diffusion Studies with Ocular Formulations of Glutathione as an Antioxidant Treatment for Ocular Diseases - María Sebastián-Morelló; Adrián M. Alambiaga-Caravaca; María Aracely Calatayud-Pascual; Vicent Rodilla; Cristina Balaguer-Fernández; María Miranda; Alicia López-Castellano (MDPI AG, 2020)
Exposure to sunlight and contact with atmospheric oxygen makes the eye particularly susceptible to oxidative stress, which can potentially produce cellular damage. In physiological conditions, there are several antioxidant defense mechanisms within the eye. Glutathione (GSH) is the most important antioxidant in the eye; GSH deficit has been linked to several ocular pathologies. The aim of this study was to explore the potential for newly developed formulations allowing controlled delivery of antioxidants such as GSH and vitamin C (Vit C) directly to the eye. We have investigated the stability of antioxidants in aqueous solution and assessed ex-vivo the diffusion of GSH through two ocular membranes, namely cornea and sclera, either in solution or included in a semisolid insert. We have also carried out the hen's egg-chlorioallantoic membrane test (HET-CAM) to evaluate the ocular irritancy of the different antioxidant solutions. Our results showed that GSH is stable for up to 30 days at 4 °C in darkness and it is not an irritant to the eye. The diffusion studies revealed that the manufactured formulation, a semisolid insert containing GSH, could deliver this tripeptide directly to the eye in a sustained manner.